Applicability of low-cost cameras for monitoring suspended sediment in rivers through close-range remote sensing - Mohammad Nasir, Muhammad Azamuddeen (2022)
Suspended sediment in rivers is a major problem globally. Monitoring of water turbidity and suspended sediment concentration (SSC) using satellites and in-situ sampling has been used widely to assess fine sediment pollution. However, due to low image resolution, application of satellite remote sensing is limited to only large water bodies, while in-situ sampling does not provide the continuous spatial data that are needed to address certain scientific questions or management problems. This research aimed to understand the potential of using low-cost cameras to estimate SSC in smaller rivers and streams and produce reach scale ‘maps’ of SSC. The study consists of development and testing of statistical models to predict SSC from pixel information contained in digital images, and validation of these models through field tests. An overarching goal was to assess the transferability of models between rivers and the effects of different camera sensors on SSC predictions. Laboratory experiments developed predictive models for two cameras (Vivo V9 smartphone and DJI Mavic Pro drone). Experiments involved manipulation of SSC in a water filled tank, with images taken with each camera and over a different coloured bed at each controlled sediment concentration. Digital Number (DN) values for each bed colour, camera and colour channel combination was extracted, with Generalised Additive Models fitted to Red, Blue and Green (R, G, B) colour bands.